Use of expected-value parameters for estimating length-weight relationship in fishes - ., Prajneshu; Ravichandran, S (Indian Journal of Fisheries, 2011)
Nonlinear estimation procedures are generally employed for determining thelength-weight relationship in fishes. As no attention is paid to reparameterizationof the parameters, the model-data set combination sometimes exhibits anextremely high nonlinear behaviour, i.e. the parameter-effects measure of curvatureis very large. The purpose of the present paper is to make use of'expected-value'parameters which depict close-to-linear behaviour. The methodology is illustratedwith the help of data taken from fisheries literature.